Intensive Behavioral Treatment of Urinary Incontinence of Children With Autism Spectrum Disorders: An Archival Analysis of Procedures and Outcomes From an Outpatient Clinic. (March 2013) - Hanney, Nicole M.; Jostad, Candice M.; LeBlanc, Linda A.; Carr, James E.; Castile, Allison J.
LeBlanc, Crossett, Bennett, Detweiler, and Carr (2005) described an outpatient model for conducting intensive toilet training with young children with autism using a modified Azrin and Foxx, protocol. In this article, we summarize the use of the protocol in an outpatient setting and the outcomes achieved with a large sample of children with autism spectrum disorders. Thirty archival clinical records were coded for several variables related to treatment implementation and outcome. The majority of participants achieved full continence in an average of approximately 2 weeks. Details on the typical implementation and course of treatment are presented to provide a profile for future practitioners.